1999
DOI: 10.1124/mol.55.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Modulation of Nicotinic Acetylcholine Receptor Currents in Cultured Cortical Neurons

Abstract: Ethanol, at physiologically relevant concentrations, significantly enhanced high-affinity neuronal nicotinic acetylcholine receptor (NnAChR) currents insensitive to alpha-bungarotoxin (alpha-BuTX-ICs) in cultured rat cortical neurons in a fast and reversible manner, as determined by standard whole-cell patch-clamp recording techniques. The enhancement was (mean +/- S.D.) 7.7 +/- 5% to 192 +/- 52% upon coapplication of 3 to 300 mM ethanol with 1 to 3 microM ACh. No plateau for this ethanol-induced enhancement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 28 publications
6
100
0
Order By: Relevance
“…Results from in vitro (32)(33)(34) and genetic studies (35)(36)(37) show that ethanol interacts directly with ␣4␤2 nAChRs (30,31). Our data suggest that varenicline reduces the efficacy of ACh activity at nAChRs, leading to a reduction in ethanol intake by decreasing the rewarding properties of ethanol.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Results from in vitro (32)(33)(34) and genetic studies (35)(36)(37) show that ethanol interacts directly with ␣4␤2 nAChRs (30,31). Our data suggest that varenicline reduces the efficacy of ACh activity at nAChRs, leading to a reduction in ethanol intake by decreasing the rewarding properties of ethanol.…”
Section: Discussionmentioning
confidence: 77%
“…Results from in vitro studies have shown that ethanol directly activates the ␣4␤2 nAChR (32)(33)(34). The ␣4 nAChR gene may influence some of the common actions of nicotine and ethanol in the mouse because a polymorphism in the gene encoding the ␣4 subunit of the nAChR (Chrna4) is associated with ethanol intake in animals (35) and modulates ethanol withdrawal (36) and the ethanol effect on acoustic startle response (35,37).…”
mentioning
confidence: 99%
“…Accordingly, the nicotinic receptor is a site at which nicotine and ethanol may interact. Corroborating this suggestion, it has been demonstrated that ethanol enhances agonist-induced ion flux through nicotinic receptors (Aistrup et al, 1999;Cardoso et al, 1999) and that ethanol-induced stimulation of mesolimbic dopamine systems involves the activation of nicotinic receptors (Soderpalm et al, 2000). Despite these findings, there have been relatively few animal studies of the basic neurobiology of the combined nicotine and ethanol exposure, and while some studies suggest that nicotine has a modulatory effect on ethanol effects through its cholinergic actions, others show no marked interactions and still others show augmented effects (Bachtell and Ryabinin, 2001;Penland et al, 2001;Tizabi et al, 2002Tizabi et al, , 2003.…”
Section: Neurobiology Of Nicotine Vs Ethanol Interactionsmentioning
confidence: 85%
“…23) This raises the question of whether nefiracetam potentiation at high ACh concentrations is due to an increase in the total receptors available for activation by rapid exocytosis of the receptors or changes in single-channel properties. The latter may include: 1) an increase in single-channel conductance; 2) an increase in open probability; 3) a prolongation of open time; and 4) a combination of any of the three.…”
Section: Nefiracetam Potentiates Nach Receptor Activitymentioning
confidence: 99%